Perempuan Penyembuh: Sebuah Pendekatan Feminis - Buce A. Ranboki (Indonesian Journal of Theology, 2018)
In Timor, the traditional healing practices of mnane (a Healer or healing woman) are alleged as “shamanism.” All the same, this accusation originates from area church as religious institution that had been founded upon Calvinistic values. What is sadder still, Healers are labeled superstitious, irrational, and profane. Such accusations marginalize and wound their dignity as women. The theological question is whether the source of such healing power would have caused the church to construct theological assumptions that would be so androcentric, rationalistic, and supremely concerned with accuracy. In this study, I would argue that the church must construct a theology that is truly born-of and favorable-toward women, as it also ushers Healers into the hospitality of the church-as-space for dialogue, partnership, and empowerment. Through the feminist approach of Mery Kolimon, the inspirational Teologi Rakyat (grassroots theology) of John Campbell-Nelson, and Trinitarian theological imagery, I urge that traditional Healers deserve enfranchisement and inclusion in the fellowship and friendship of the church as both form and function of the ‘Church's sacramental’ for the work of empowerment and healing.